Increased Hardness Value of Medium Manganese Steel Through Double Tempering, Hot Rolling, and Variation of Cooling Media - Tjahjono, Arif; Pramesti, Firly Giska; Frendyta, Nadya Salsabila; Paristiawan, Permana Andi (Jurnal Ilmu Fisika, 2024)
Research has been conducted to enhance the hardness value of medium manganese steel through a heat treatment. Initially, this process begins with austenization at a temperature of 900°C, followed by tempering at 650°C and double tempering at 600°C, with each stage lasting 30 minutes. Subsequently, each stage concludes with a hot rolling process, after which air or water cools the material. As a result of these processes, the hardness tests revealed an increase in the hardness of medium manganese steel, reaching up to 389.70 BHN with a tensile strength of 827 MPa, which was notably achieved through air cooling. This significant increase in hardness is attributed to the emergence of the martensite phase and the presence of a large number of carbides, which are more evenly distributed after the double-tempering process. Additionally, small amounts of carbides were observed in the austenite matrix. Upon examination of the SEM fractography results, it was revealed that the fracture was mixed, with a cleavage area slightly larger than the dimple area. This observation suggests that despite its high hardness value, the sample retains good toughness.